Patnog the persistence of a post-burial practice in Talisay, Pandan, Antique. - Dioso, Sashah B.
This paper is a study about the continous existence of a pos-burial practice called patnog in the community of Talisay, Antique. This aims to: document and describe the persistent pattern the ritual's practice in the said community; identitfy the beliefs and related ritual that underlies it; identify and discuss the status of manogpatnog; identify the factors responsible for its persistence. The paper explores both the indigenous and Catholic nature of the practice., Information is primarily taken from interviews with key respondents using informal interview. The researcher, as part of the community where the patnog exist, employs participant-observation technique. The study reveals that though the patnog is very indigenous in nature, the presence of Catholic elements is very evident. The continuing existence of the ritual is attributed to the fact that it is considered as a tradition which needs to be practice by the people in the said community. The status of the manogpatnog goes with that of the patnog also. He is considered only as part of a tradition that should be continued. In this research, it is recommended to further the study about the patnog on the changes it underwent through time. further study should also be conducted to find out if the said ritual and rituals of similar type are being practiced in neighboring places before